2022
DOI: 10.1186/s13054-022-04082-1
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilation in COVID-19 patients aged ≥ 70 years—a prospective multicentre cohort study

Abstract: Background Noninvasive ventilation (NIV) is a promising alternative to invasive mechanical ventilation (IMV) with a particular importance amidst the shortage of intensive care unit (ICU) beds during the COVID-19 pandemic. We aimed to evaluate the use of NIV in Europe and factors associated with outcomes of patients treated with NIV. Methods This is a substudy of COVIP study—an international prospective observational study enrolling patients aged ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…In this subgroup the 30-day mortality reached nearly 50% in non-COVID patients and more than 70% in patients with COVID-19. This may be a least partially related to longer exposure to NIV which is associated with patient self-inflicted lung injury potentially leading to worse outcomes [ 7 , 28 ]. On the other hand, our analyses showed that the 30-day mortality of patients who required invasive mechanical ventilation was similar regardless of previous NIV attempt in both cohorts while some previous studies showed that early intubation may even be associated with worse outcomes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this subgroup the 30-day mortality reached nearly 50% in non-COVID patients and more than 70% in patients with COVID-19. This may be a least partially related to longer exposure to NIV which is associated with patient self-inflicted lung injury potentially leading to worse outcomes [ 7 , 28 ]. On the other hand, our analyses showed that the 30-day mortality of patients who required invasive mechanical ventilation was similar regardless of previous NIV attempt in both cohorts while some previous studies showed that early intubation may even be associated with worse outcomes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of NIV failure in patients with non-COVID ARDS was relatively high and correlated with ARDS severity [ 6 ]. Initial reports confirmed NIV to have a low success rate in the treatment of hypoxemic respiratory failure due to COVID-19 [ 6 , 7 ]. Randomised controlled trials showed, albeit inconsistently, that NIV compared to high-flow oxygen therapy and conventional oxygen therapy reduced the need for intubation but did not reduce mortality [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The failure of "very early" intubation at the outset of the pandemic, and the subsequent overestimated mortality from using IMV, likely led to significantly increased use of NIV and HFNO for longer durations to avoid intubation. However, accumulating evidence suggests "delaying" intubation in patients with COVID-19-associated respiratory failure is also associated with a higher mortality (21)(22)(23)(24)(25). In a cohort of 574 ICU patients with COVID-19, "very late" intubation (beyond 5 d of HFNO or NIV initiation) had Commentary the rate of mortality (87%) (26).…”
mentioning
confidence: 99%
“…We thank Shen and colleagues for their interest in our paper on the use of noninvasive ventilation in older adults with COVID-19 [ 1 ].…”
mentioning
confidence: 99%